Value of Preoperative MRI and Examination under Anesthesia for Differentiating Complete from Partial Anterior Cruciate Ligament Tears - Cavinatto, Leonardo; Gupta, Sunny; Morgan, Craig; Bartolozzi, Arthur R. (The Journal of Knee Surgery, 2019)
Partial tears of the anterior cruciate ligament (ACL) recently regained attention due to a better understanding of the two distinct bundles of the ligament and the possibility of single-bundle reconstruction procedures. An accurate diagnosis is important as it influences treatment options and patient prognosis. The aim of this study was to evaluate the value of examination under anesthesia (EUA) and magnetic resonance imaging (MRI) for differentiating partial from complete ACL tears. For this purpose, this prospective case series included 95 consecutive patients undergoing primary ACL reconstruction surgeries. MRI, EUA, and MRI combined with EUA were performed preoperatively, and results were compared with arthroscopy. Our data showed that ACL lesions were diagnosed as partial tears in 42.1% (n = 40) of EUA, 23.2% (n = 22) of MRI, and 11.6% (n = 11) of arthroscopies. EUA and MRI demonstrated sensitivity of 100 and 90.1%, and specificity of 65.5 and 85.6%, respectively. Combined EUA and MRI demonstrated sensitivity of 100% and specificity of 83.1%. Our study revealed that preoperatively MRI and EUA may help surgeons early identify partial ACL tears and influence treatment decisions.
Keywords: anterior cruciate ligament; partial tears; diagnostic tool; examination under anesthesia; magnetic resonance imaging